Dental stem cells: a future asset of ocular cell therapy. (10th November 2015) - Yam, Gary Hin-Fai; Peh, Gary Swee-Lim; Singhal, Shweta; Goh, Bee-Tin; Mehta, Jodhbir S.
Abstract : Regenerative medicine using patient's own stem cells (SCs) to repair dysfunctional tissues is an attractive approach to complement surgical and pharmacological treatments for aging and degenerative disorders. Recently, dental SCs have drawn much attention owing to their accessibility, plasticity and applicability for regenerative use not only for dental, but also other body tissues. In ophthalmology, there has been increasing interest to differentiate dental pulp SC and periodontal ligament SC (PDLSC) towards ocular lineage. Both can commit to retinal fate expressing eye field transcription factors and generate rhodopsin-positive photoreceptor-like cells. This proposes a novel therapeutic alternative for retinal degeneration diseases. Moreover, as PDLSC shares similar cranial neural crest origin and proteoglycan secretion with corneal stromal keratoctyes and corneal endothelial cells, this offers the possibility of differentiating PDLSC to these corneal cell types. The advance could lead to a shift in the medical management of corneal opacities and endothelial disorders from highly invasive corneal transplantation using limited donor tissue to cell therapy utilizing autologous cells. This article provides an overview of dental SC research and the perspective of utilizing dental SCs for ocular regenerative medicine.